Experimental behaviour of Wire‐and‐Arc Additively Manufactured stainless steel rods. Issue 2 (1st September 2021) - Laghi, Vittoria; Palermo, Michele; Silvestri, Stefano; Gasparini, Giada; Trombetti, Tomaso
Abstract: Recently, metal Additive Manufacturing has gained great importance in many industrial sectors with first pioneering applications in also in the Construction field. In particular, a weld‐based technique called Wire‐and‐Arc Additive Manufacturing (WAAM) allows to build real‐scale structural elements of complex geometry thanks to 6‐axes robotic arms and off‐the‐shelf welding equipment able to print at higher speed thus overcoming the geometrical constraints typical of other 3D printing technologies such as Powder Bed Fusion. Nonetheless, the printing outcomes need to be properly characterized both in terms of their specific material properties, which substantially differ from the feedstock, and the geometrical imperfections proper of the printing process. Among possible deposition strategy for WAAM the dot‐by‐dot printing results to be particularly suitable to realize metal 3D lattice structures made by straight rods. This novel dot‐by‐dot printing could bring to different mechanical parameters with respect to the layer‐by‐layer deposition (widely known and studied in the literature and already adopted for first practical applications). This work presents the first results of a wide experimental investigation carried out at University of Bologna to study the geometrical imperfections and the main mechanical properties (through tensile and compression tests) of WAAM‐produced stainless steel rods of different lengths. First indications are given on the influence of the rods length on the compression capacity Future work is aimed at quantifying the influence of geometrical irregularities (initial crookedness and cross‐section variation) and non‐linear material behavior in the compression response of 3D‐printed rods through numerical studies to calibrate a set of ad‐hoc buckling curves.